Enhancing Reading Interest of Elementary School Students through Electronic Children’s Books - Ayati (Fakultas Ilmu Pendidikan dan Budaya - Universitas Bina Mandiri Gorontalo, 2025)
Elementary school students’ reading interest remains relatively low, partly due to the limited use of varied and technology-based learning media. Electronic children’s books have the potential to enhance students’ reading interest through attractive visual features and easy accessibility. However, in elementary school learning practices, the use of electronic books is still limited, resulting in reading interest that has not developed optimally. This study aimed to enhance students’ reading interest through the use of electronic children’s books. This research employed Classroom Action Research (CAR) conducted at SDN Negeri 9 Paleleh Barat and implemented in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation and reading interest questionnaires. The results showed an improvement in students’ reading interest, as indicated by increased enthusiasm, participation, and engagement in reading activities. These findings indicate that the use of electronic children’s books is effective in enhancing reading interest among elementary school students.